Renegotiating the Islam and Development-Nexus in Indonesia: Fikih Peradaban as a Middle Ground between Local and Global Development Paradigms - tho Seeth, Amanda (ISLAM NUSANTARA:Journal for the Study of Islamic History and Culture, 2023)
I n 2015, the United Nations introduced the that aims at globally achieving concrete Sustainable Development Goals (SDGs). Today, sustainable development has become the dominant development narrative in 2030 Agenda, a new development paradigm international cooperation discourse, despite criticism of its top-down approach and secular bias. This explorative article discusses the potential of Indonesian Islamic concepts, such as Nahdlatul Ulamaâ€™s Islam Nusantara and Fikih Peradaban, to contribute to the sustainable development discourse from an Islamic perspective. By mapping the current intellectual debate on Fikih Peradaban, I demonstrate that Fikih Peradaban is a particularly suited approach as epistemologically and conceptually it occupies a middle ground position that mediates between local and global development paradigms. I further argue that Fikih Peradabanâ€™s focus on the concepts of humanism, humanist Islam (or Islamic humanism), and Islamic legal reasoning in the service of all people regardless of religious affiliation may contribute to its global appeal and effectiveness. The article draws on notes taken at a conference on â€œIslam Nusantara and World Peaceâ€ (February 5, 2023) in Surabaya as well as notes taken at the first Fikih Peradaban conference (February 6, 2023) in Surabaya. It is also based on a close reading of official material that accompanied the latter conference. Furthermore, I embed the discussion on the nexus between Indonesian Islamic concepts and sustainable development into the broader academic and policy debate on the role of religion within sustainable development. Hence, this article is connected to the research project â€œFreedom and Development? Religious Actors, Freedom of Religion and Belief, and Sustainable Developmentâ€ conducted by the German Institute for Global and Area Studies, Hamburg, from 2020 to 2023. Keywords: Indonesia, Fikih Peradaban, humanist Islam, sustainable development